Analisis Kesulitan Membaca pada Siswa Kelas 1 Sekolah Dasar 03 Lubuk Begalung - Yola Zefni Putri; Adrias Adrias; Aissy Putri Zulkarnanini (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The purpose of this study was to describe and analyze the challenges faced by grade 1 elementary school students in beginning reading and to identify the factors that cause them. This study used a qualitative approach with a descriptive method. To collect data, interviews were conducted with grade 1 teachers who were the subjects in this study. The results showed that grade 1 elementary school students faced difficulties when starting to read, especially in identifying letters, blending consonants, and reading fluently. Students' intellectual abilities, intelligence, and cleverness were relatively low, reduced interest in learning to read, little desire to start reading, and lack of attention from parents were some of the factors that hindered them in learning to read. Therefore, it can be concluded that some students in grade 1 of SDN 03 Lubuk Begalung still experience difficulties in starting reading skills.